MHD free convection heat transfer in nano-fluid flow in square porous cavity of TiO2 nanoparticles with base fluid engine oil - Zafar, Mudasar; Hamzah, Sakidin; Sheremet, Mikhail A.; Iskandar, Dzulkarnain; Roslinda, Mohd Nazar; Al-Yaari, Abdullah; Mohd Zuki, Salleh (Semarak Ilmu Publishing, 2023)
In this article, the MHD-free convection heat transfer behaviour of oil-based nanofluids is explored numerically inside a square cavity enclosure filled with a porous material. The governing equations are derived using Brinkman and Buongiorno’s two-phase nanofluid models. We developed the mathematical model for the over-research problem for heat transfer enhancement applications; the finite volume approach was used to solve dimensionless governing equations. The SIMPLE algorithm is used to calculate the values of pressure and velocity. The investigation of nanofluid with engine oil in the presence of magnetic field in square cavity for the thermal application is not studies. The following parameters are investigated to find out the heat transfer analysis: Ra = 0, porosity = 10, initial volume concentrations Ø= 0–0.05, constant angle of magnetic field Ý= 0, Hartmann Number Ha = 0,100, Prandtl Number Pr = 0.8. The results are also compared with existing literature. It is also indicated that the effect of Nusselt number is very interesting at different values of Ra, i.e., heat transfer rate increases when volume fraction increases at the contact hot wall of the cavity, but reverse phenomena are observed at the cold wall.